Penyuluhan Dampak Penggunaan Gadget pada Anak Usia 6 – 12 Tahun di TPQ Nurul Ilmi Kota Makassar - Nur Inayah Rauf; Andi Mutiah Sari; Muhajrin Muhajrin (Lembaga Pengembangan Kinerja Dosen, 2025)
Entering the digital era, technology plays an important role in human life. The Covid-19 pandemic in 2020 accelerated the digital transformation, including the activities of school children aged 6-12 years. The use of gadgets can have both positive and negative impacts on children, so it is necessary for parents to play a role in managing screen time to maximise the positive impact and minimise the negative impact of gadget use on children. This activity is a counselling for parents, children, and teachers conducted at TPQ Nurul Ilmi Makassar City. The methods used were lectures and discussions. The results of the activity were 25 parents and children, as well as 5 teachers who participated in counselling activities. Based on the results of the discussion, the use of gadgets can help children in finding learning resources and as an educational medium for children, some parents supervise and limit screen time for children but there are also some parents who cannot supervise optimally because they are busy working. Children are given gadgets with the hope that parents can contact their children easily. The advice given to parents is to limit screen time for children to a maximum of 2-3 hours per day and select applications and what children watch during screen time. Meanwhile, teachers need to develop learning methods so that children are more comfortable learning and playing than using gadgets.